Complex proteinopathies and neurodegeneration: insights from the study of transmissible spongiform encephalopathies - Piccardo, Pedro; Asher, David M. (Arquivos de Neuro-Psiquiatria, 2018)
Protein misfolding diseases are usually associated with deposits of single “key” proteins that somehow drive the pathology; β-amyloid and hyperphosphorylated tau accumulate in Alzheimer's disease, α-synuclein in Parkinson's disease, or abnormal prion protein (PrPTSE) in transmissible spongiform encephalopathies (TSEs or prion diseases). However, in some diseases more than two proteins accumulate in the same brain. These diseases might be considered “complex” proteinopathies. We have studied models of TSEs (to explore deposits of PrPTSE and of “secondary proteins”) infecting different strains and doses of TSE agent, factors that control incubation period, duration of illness and histopathology. Model TSEs allowed us to investigate whether different features of histopathology are independent of PrPTSE or appear as a secondary result of PrPTSE. Better understanding the complex proteinopathies may help to explain the wide spectrum of degenerative diseases and why some overlap clinically and histopathologically. These studies might also improve diagnosis and eventually even suggest new treatments for human neurodegenerative diseases.
Keywords: Dementia; amyloidogenic proteins; prion diseases